Correlated leading baryon-antibaryon production in e+e−→cc[bar]→Λ+cΛ[bar]−cX - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a study of 649±35 e+e−→cc[bar] events produced at √s≈10.6 GeV containing both a Λ+c baryon and a Λ[bar]−c antibaryon. The number observed is roughly 4 times that expected if the leading charmed hadron types are uncorrelated, confirming an observation by the CLEO Collaboration. We find a 2-jet topology in these events but very few additional baryons, demonstrating that the primary c and c[bar] are predominantly contained in a correlated baryon-antibaryon system. In addition to the charmed baryons we observe on average 2.6±0.2 charged intermediate mesons, predominantly pions, carrying 65% of the remaining energy.